2001
DOI: 10.1074/jbc.m103401200
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Characterization and Ionic Stoichiometry of the Rat Brain K+-dependent Na+/Ca2+ Exchanger, NCKX2

Abstract: ؉ inhibited the inward currents by a maximum of 40%, with a K1 ⁄2 of 2 mM or less, depending upon the conditions. The transport stoichiometry of NCKX2 was determined by observing the change in reversal potential as individual ion gradients were altered. Our data support a stoichiometry for rat brain NCKX2 of 4 Na ؉

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
49
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 46 publications
(47 reference statements)
9
49
0
Order By: Relevance
“…In situ studies on the properties of the NCKX cation transport sites have only been carried out on the NCKX1 exchanger in retinal rod outer segments (reviewed in Refs. 4,15,16), while several studies have reported on the cation concentration dependence of heterologously expressed NCKX1 (dolphin, chicken), NCKX2 (chicken, human, rat), Caenorhabditis elegans NCKX, and a NCKX1 deletion mutant from which the two large hydrophilic loops (ϳ63% of the total sequence) were removed (9,13,14,17,18). The values obtained in situ for NCKX1 and in heterologous systems for the various NCKX isoforms mentioned above were quite similar.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…In situ studies on the properties of the NCKX cation transport sites have only been carried out on the NCKX1 exchanger in retinal rod outer segments (reviewed in Refs. 4,15,16), while several studies have reported on the cation concentration dependence of heterologously expressed NCKX1 (dolphin, chicken), NCKX2 (chicken, human, rat), Caenorhabditis elegans NCKX, and a NCKX1 deletion mutant from which the two large hydrophilic loops (ϳ63% of the total sequence) were removed (9,13,14,17,18). The values obtained in situ for NCKX1 and in heterologous systems for the various NCKX isoforms mentioned above were quite similar.…”
mentioning
confidence: 49%
“…The first four mammalian NCKX isoforms and those cloned from lower organisms have been shown to code for K ϩ -dependent Na ϩ /Ca 2ϩ exchangers when expressed in cell lines and transcripts are found in a wide variety of tissues (2). NCKX1 and NCKX2 carry out K ϩ and Ca 2ϩ cotransport and Na ϩ and Ca 2ϩ countertransport at a stoichiometry of 4Na ϩ : 1Ca 2ϩ ϩ 1K ϩ (3,13,14). This study concerns identification of residues involved in cation transport via the NCKX Na ϩ /Ca 2ϩ -K ϩ exchanger.…”
mentioning
confidence: 99%
“…Reverse and forward I NCKX were recorded using a holding potential of 0 mV. The I NCKX was recorded, according to Dong et al (2001), starting from a holding potential of 0 mV to a short-step depolarization at ϩ80 mV (60 ms). Then, a descending voltage ramp from ϩ80 mV to Ϫ80 mV was applied.…”
Section: Electrophysiologymentioning
confidence: 99%
“…NCKX2, NCKX3, and NCKX4 are broadly expressed in brain with distinct, often overlapping, regional distributions . The expression of NCKX2, the major neuronally expressed isoform (Tsoi et al, 1998;Dong et al, 2001), is limited to cone photoreceptors (Prinsen et al, 2000) and to neurons, where it plays important physiological roles (Tsoi et al, 1998;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These functional properties were subsequently confirmed for recombinant NCKX1 and 2 using either 45 Ca 2+ uptake into insect cells or electrophysiological recordings in HEK293 cells (11,55,57). Furthermore, NCKX1 and 2 display similar apparent affinities for Ca 2+ (~1-2 M), K + (15-40 mM), and Na + (20-60 mM) (11,47). Based on sequence identity, the other NCKX family members are expected to display the same stoichiometry.…”
Section: Structure and Functionmentioning
confidence: 70%